Analisis Tanggung Jawab Hukum Perusahaan Tambang Timah Terhadap Kerugian Kerusakan Lingkungan (Studi: di Provinsi Kepulauan Bangka Belitung) - Alpian Akbar; Yandi Yandi; Cik Marhayani (Jurnal Hukum Lex Generalis, 2025)
Tin mining activities in the Bangka Belitung Islands Province have significantly contributed to regional economic growth but have also caused severe environmental degradation. The main legal issue arises from the weak implementation of post-mining land reclamation obligations by tin mining companies, despite being clearly regulated under Law No. 3 of 2020 on Mineral and Coal Mining, Law No. 32 of 2009 on Environmental Protection and Management, and Law No. 40 of 2007 on Limited Liability Companies. This study aims to analyze the legal responsibilities of tin mining companies regarding post- mining land reclamation under Indonesia’s corporate legal system and to examine the legal consequences for companies that fail to fulfill such obligations within the framework of sustainable business responsibility. This research employs a normative juridical method with a business law and environmental law approach, supported by an analysis of legislation, legal doctrines, and literature review. The results show that the legal responsibility of tin mining companies includes administrative, civil, and criminal liabilities for negligence in reclamation activities. Normatively, reclamation implementation reflects the application of the corporate liability and strict liability principles, as well as the realization of Corporate Social and Environmental Responsibility (CSER) and Good Corporate Governance (GCG) within corporate law. Empirically, however, the enforcement of reclamation obligations remains weak due to limited supervision and law enforcement, resulting in a gap between legal norms and actual practice. This study concludes that the implementation of post-mining reclamation obligations is not merely a legal duty but also a moral and social responsibility of corporations to achieve sustainable, just, and environmentally conscious mining practices.